Pengaruh Pupuk Kandang Sapi dan Kieserite terhadap Pertumbuhan dan Hasil Tanaman Padi (Oryza sativa L.) Metode SRI - Hanafi, Fakhri; Rozen, Nalwida (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2024)
This research has been conducted on January up to June 2020 in the fields of suboptimal Pasar Ambacang Subdistrict Kuranji Padang. The purpose of this study was to determine the interaction between cow manure and kieserite, determine dose of cow manure is the best and know the best of doses of fertilizer kieserite the best on plant growth of rice cropping with SRI systems. this research using 2 factors in a complete random design. The first factor is the dose of cow manure which consists of 2 levels, namely: 5 ton/ha and 10 ton/ha, while the second factor is the dose of fertilizer kieserite which consists of 3 levels, namely: 0 kg/ha, 75 kg/ha and 150 kg/ha. Observation data is analyzed with partial range of the F test 5%. If the value of calculated F is greater than F 5%, then proceed with the test further Duncan’s Multiple Range Test (DMRT) on the real level of 5%. Every each observation the results obtained from each treatment of manure and kieserite did not affect the growth and results in rice plants with SRI method